THE RELATIONSHIP BETWEEN NURSES’ CARING BEHAVIOR AND PATIENT SATISFACTION - Nauwys, Joselita Meryline; Kurniawan, Ardhiles Wahyu; Hastuti, Apriyani Puji (HEARTY, 2026)
Caring in nursing is practice professional nursing , knowledge , awareness , values and satisfaction patient from performance service health benefits​ after patient compare what you get with what is expected . Research This aim For want to know connection between behavior caring nurse patients at Jailolo Regional General Hospital with level satisfaction respondents . Research This is study descriptive correlative with approach quantitative research​ done in the room care Jailolo Regional General Hospital in June - July 2022 with amount sample of 90 respondents . The instrument used For measure satisfaction is instrument Patient Satisfaction Questionnaire ( PSQ ) , meanwhile behavior caring nurse by patient measured with Questionnaire Caring Nurses . Research This describe that that part big 61 respondents ( 67.8%) rated that behavior caring nurse at Jailolo Regional General Hospital Already good , 25 people (27.8%) in category enough , 4 respondents (4.4%) in category less . Image results satisfaction patient very satisfied 45 people (50%) , satisfied 36 people ( 40% ), no satisfied 4 people (4.4%) and enough satisfied 5 people (5.6%) against service nurses there. Correlation test using Pearson, obtained results that p-value = 0.000 and r value = 0.597 ( correlation medium ) there is correlation between caring nurses with satisfaction patient p-value = 0.000 and r value = 0.597 ( correlation moderate ). From the research this , can concluded that behavior caring nurse influence satisfaction patients in the Inpatient Ward of Jailolo Regional General Hospital . Increasingly tall the caring value of nurses , then the more high satisfaction​ patient.